Формування вхідного струму в системі «мережа - вхідний LC-фільтр – матричний перетворювач – асинхронний двигун» в ковзному режимі - Мисак, Тарас Володимирович; Михальський, Валерій Михайлович (НТУ "ХПІ", 2013)
The object of study is the matrix converter controlled in sliding mode with input LC-filter and induction motor as the load. The use of the vector approach under control synthesis in a sliding mode allows providing high quality output voltage and close to sinusoidal inputting current. A digital model has been constructed with studying the electromagnetic processes. The recommendations for the practical implementation of the control system allowing for the real sliding mode are given.
Keywords: МП традиційної топології; силові напівпровідникові прилади; цифрові сигнальні процесори; цифрові моделі; ключі змінного струму; векторний метод керування